Analysis of whatsapp call center WA MAILAKU-based public service through indrajit’s e-government model: a case study of the UPTD - Anggun Candra Cahyani, Ni Komang Yudha; Anak Agung Ngurah Eddy Supriyadinata Gorda (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
This study aims to analyze the public service provided through the WA MAILAKU WhatsApp Call Center using Indrajit’s e-government model at the UPTD. Training and Education for Cooperatives, Micro, Small, and Medium Enterprises. It emphasizes that WhatsApp-based service delivery should be critically examined through the e-government framework, particularly in terms of policy support, organizational capacity, and service value. This research employs a qualitative approach with a case study design. Data were collected through interviews, observation, and documentation, and were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings indicate that the implementation of WA MAILAKU is supported by leadership commitment, the existence of standard operating procedures, and the use of WhatsApp as a platform familiar to service users. The study concludes that WA MAILAKU cannot yet be fully understood as a formal e-government system, but rather as a digital public service innovation with strong potential to support fast and inclusive service delivery. Its effectiveness continues to depend on improvements in technical service management, the digital competencies of personnel, and the protection of information privacy and security. This study is limited by its focus on a single organizational unit and by its reliance on qualitative self-reported data from informants.